2022
DOI: 10.3847/1538-4357/ac57c2
|View full text |Cite
|
Sign up to set email alerts
|

The Extremely Buried Nucleus of IRAS 17208–0014 Observed at Submillimeter and Near-infrared Wavelengths

Abstract: The ultraluminous infrared galaxy IRAS 17208−0014 is a late-stage merger that hosts a buried active galactic nucleus (AGN). To investigate its nuclear structure, we performed high-spatial-resolution ( ∼ 0.″04 ∼ 32 pc) Atacama Large Millimeter/submillimeter Array (ALMA) observations in Band 9 (∼450 μm or ∼660 GHz), along with near-infrared AKARI spectroscopy in 2.5–5.0 μm. The Band 9 dust continuum peaks at the AGN location, and toward this position CO(J = 6 − 5) and CS(J = 14 − 13) are detected in absorption. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 122 publications
0
14
0
Order By: Relevance
“…Furthermore, our results imply that a hot dust (T d ∼ 1000 K) component in a central sub-parsec region can exist in the near-IR source, we expect to be observed by molecular CO absorption lines in ultra-luminous infrared galaxies (e.g., Baba et al 2018Baba et al , 2022Onishi et al 2021) and Seyfert galaxies (Uzuo et al 2021;Matsumoto et al 2022).…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, our results imply that a hot dust (T d ∼ 1000 K) component in a central sub-parsec region can exist in the near-IR source, we expect to be observed by molecular CO absorption lines in ultra-luminous infrared galaxies (e.g., Baba et al 2018Baba et al , 2022Onishi et al 2021) and Seyfert galaxies (Uzuo et al 2021;Matsumoto et al 2022).…”
Section: Discussionmentioning
confidence: 56%
“…Imanishi et al (2010) reported the AKARI CO absorption depth τ (CO) = 0.5. Here, τ(CO) is the apparent depth of the blended CO feature measured at the bottom of the blended R-branch feature 9 , and is often used as an indicator of the absorbing CO column density without careful analysis using LTE spectral modeling (Spoon et al 2004;Baba et al 2018Baba et al , 2022. We note, however, that τ(CO) is proportional to the CO column density only until individual CO absorption lines are saturated; once saturated, it increases with the line (velocity) width (see Baba et al 2018 for the demonstration).…”
Section: Comparison With the Akari Low-resolution Spectrummentioning
confidence: 99%
“…The AKARI spectroscopy is particularly efficient for detecting the CO absorptions in low-redshift galaxies due to its wavelength coverage below 5 μm. Our sample comes mainly from Baba et al (2022), who compiled the AKARI CO measurements, and two others with other CO measurements. We specifically compare galaxies with either deep CO absorption, enhanced vibrationally excited HCN emission at submillimeter wavelengths, or both.…”
Section: Comparison With Galaxies With Previous Rovibrational Co Meas...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although this galaxy is detected in the hard X-ray with NuSTAR and Chandra, it is inconclusive from analysis of the X-ray spectra whether a buried AGN is present et al 2013). It has been argued in several studies that the system likely hosts buried AGNs (e.g., Iwasawa et al 2011;Falstad et al 2021;Baba et al 2022). The brightest region on the west is located at the dynamical center of the molecular gas as revealed by ALMA (2018.1.00486.…”
Section: Appendix a Notes On Individual Systemsmentioning
confidence: 99%